Live streaming of Constitution Bench Hearings: A Step closer to e-Governance and Justice - Kumar, Ravinder; Malik, Aakash (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2023)
The live streaming of Constitution Bench hearings is a research topic that explores the feasibility and potential benefits of broadcasting the proceedings of the highest judicial forum in India. The Constitution Bench of the Supreme Court of India is responsible for interpreting the country’s constitution and delivering landmark judgments that shape the legal landscape. However, the lack of transparency and accessibility in the functioning of the judiciary has been a longstanding concern in India. This research aims to investigate the feasibility of live-streaming Constitution Bench hearings to enhance transparency, accountability, and public participation in the judicial process. The study examines the legal and technological challenges associated with live streaming and the potential benefits and drawbacks of the practice. By analyzing the experiences of other countries that have implemented live streaming of court proceedings, the study aims to provide policy recommendations and suggest a roadmap for implementing live streaming in India. Ultimately, the research seeks to contribute to the ongoing discourse on judicial reforms and the democratization of the Indian judiciary.